POLITENESS STRATEGIES IN DIGITAL CONVERSATION: A PRAGMATIC ANALYSIS OF BRENÉ BROWN’S INTERVIEW ON THE TIM FERRISS SHOW (2020) - Halimah Nuchbaiti (Philosophica: Jurnal Bahasa, Sastra, dan Budaya, 2026)
This study explores the use of politeness strategies in an episode of The Tim Ferriss Show featuring Dr. Brené Brown, using the theoretical framework of Brown and Levinson (1987). The research aims to identify the politeness strategies employed during the conversation and how these strategies function in maintaining respectful and meaningful interaction. This study employed a descriptive qualitative method to examine 20 utterances from the podcast, with 10 of them analyzed in depth. The findings reveal the application of four politeness strategies: bald on record, positive politeness, negative politeness, and off-record. Among these, positive politeness was the most frequently used, indicating the speakers’ effort to communicate clearly while fostering connection. In addition to verbal expressions, non-verbal cues such as tone and facial expressions contributed to the politeness conveyed. This research concludes that politeness strategies play a crucial role in digital discourse, supporting effective communication and social harmony. Keywords: politeness strategies, pragmatics, podcast, Brown and Levinson, digital communication.